Pelatihan Penggunaan Google Workspaces dan AI untuk Peningkatan Kompetensi Guru Raudhatul Athfal: Training on Using of Google Workspace and AI to Improve the Competence of Raudhatul Athfal Teachers - Nugraha, Ucu; Nugraha, Rikky Wisnu; Amalia, Endang; Hamdani, Dani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The advancement of digital technology requires improved competencies among educators, including teachers at Raudhatul Athfal (RA), to optimize the learning process. This community service program aims to enhance the skills of RA teachers in utilizing Google Workspaces and to introduce the use of artificial intelligence (AI) tools, specifically ChatGPT, in the development of teaching materials. The methods employed include needs assessment through observation and interviews, module development, hands-on training, practical sessions for creating digital learning materials, and evaluation through questionnaires. The activity was conducted at the RA Al Hidayah Hall in Pangandaran, with the participation of 47 teachers. The results of the questionnaire evaluations and participant feedback showed a significant improvement in the participants' ability to use digital platforms to support innovative learning. This program demonstrates that practice-based training is efficacious in improving the digital literacy of RA teachers and has the potential to be replicated in other regions to support the transformation of early childhood education.